Screening of aphrodisiac property in sea slug, aplysia dactylomela - Hashim, Ridzwan; Mohd Roslan, Noor Atika Elliyana; Zulkipli, Farah Hanis; Mohd Daud, Jamaluddin (Elsevier (Singapore) Pte Ltd, 2014)
Objective: To evaluate the aphrodisiac property of Aplysia dactylomela (A. dactylomelan), locally known as 'dugu-dugu', which is one of the sea slug species. Methods: Two types of extractions were used: aqueous and lipid. Three doses of each A. dactylomelan extract, respectively; 50, 100, 200 mg/kg were administered (i.p.) to male mice for mounting behavior test. Sildenafil citrate or Viagra(R) (5 mg/kg) being positive control while negative control received saline solution. Results: The animals treated with lipid extract at the respective dose exhibited mounting behavior, but the mounting frequency decreased at higher doses (100 and 200 mg/kg). However, all doses of aqueous extract did not show any mounting behavior. Meanwhile, in all doses of lipid extracts administered displayed significant difference 9P<0.05) from the positive control. Despite this, only the lipid extract of 50 mg/kg showed significant difference (P<0.05) with negative control. This signifies that lipid extracts especially in dose 50 mg/kg have a substantial effect of aphrodisiac property. In addition, the presence of steroids was detected in the phytochemical screening of lipid extract. Conclusions: The findings from this study provides preliminary scientific evidence that A. dactylomela could be used as an alternative medication of natural product for promoting sexual activity in men.